The Dynamics of Investments in Young Children - Trostel, Philip (Maine Policy Review, 2009)
Philip Trostel presents compelling evidence of the importance of early investment in young children, citing research demonstrating the economic and social benefits of such investments. He suggests that the lack of understanding of the cause-and-effect relationship between early childhood experiences and later-life consequences and a failure to conceptualize how things might be done in new ways are both obstacles. Trostel argues that investing in early childhood development benefits children for the rest of their lives, benefits government with reduced spending in other areas, and moreover is the “right thing to do.”
Keywords: Maine; early childhood; early intervention